1969
DOI: 10.3758/bf03209553
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile masking: Some spatial and temporal aspects

Abstract: Threshold elevations (TE) The few studies that have dealt with problems of intrasensory interaction on the skin with the standard masking procedure have confined stimulation to a relatively circumscribed area of the body, i.e., the fingers, hands, and forearms (Halliday

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 13 publications
5
52
0
Order By: Relevance
“…They found no interference when the nontarget was presented to the right hand; however, they also found no interference when the nontarget was placed closer to the target, so it is difficult to draw a definite conclusion from this study about the effect of presenting target and nontarget stimuli to quite distant sites on the skin. As noted before, in a study on masking in which subjects attempted to detect a target on one location on the fingers and ignore a masking stimulus presented to another location, more interference occurred when stimuli were presented to the same hand than when they were presented to different hands (Gilson, 1969).…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…They found no interference when the nontarget was presented to the right hand; however, they also found no interference when the nontarget was placed closer to the target, so it is difficult to draw a definite conclusion from this study about the effect of presenting target and nontarget stimuli to quite distant sites on the skin. As noted before, in a study on masking in which subjects attempted to detect a target on one location on the fingers and ignore a masking stimulus presented to another location, more interference occurred when stimuli were presented to the same hand than when they were presented to different hands (Gilson, 1969).…”
Section: Methodsmentioning
confidence: 78%
“…Intuitively, it would seem to be easier to ignore a nontarget when it is presented at some distance from the target site. However, in a study of detection masking, Gilson (1969) showed that there was no difference in the amount of interference when the masking stimulus was moved from a site adjacent to the target site to a nonadjacent site. There was a decline in masking when the masking stimulus was presented to the opposite hand.…”
mentioning
confidence: 99%
“…In particular, the extent to which a vibrotactile distractor will interfere with discrimination responses for vibrotactile targets depends on the relative separation of the two hands in external space: The closer the distractor is to the target, the harder it is for people to ignore it. Similar spatial modulations of congruency (or flanker interference) effects have been reported within other sensory modalities, such as audition and vision (e.g., Chan et al, 2004;Eriksen & Eriksen, 1974; see Styles, 1997, for a review), and also in numerous previous studies of intramodal tactile selective attention (e.g., Craig, 1974;Gilson, 1969;Weisenberger, 1994;Weisenberger & Craig, 1982). However, these earlier studies often manipulated spatial distance in somatotopic and abstract reference frames at the same time, and therefore, the question of which frame of reference is relevant during tactile spatial selective attention remained unanswered.…”
Section: Spatial Modulation Of Tactile Selective Attentionmentioning
confidence: 79%
“…Numerous studies have shown that a person's ability to detect or identify a tactile stimulus presented to a particular location on the skin can be impaired if a distractor stimulus is presented from a nearby skin site (e.g., Craig, 1974;Gilson, 1969;Horner, 1995Horner, , 1997Weisenberger, 1994;Weisenberger & Craig, 1982). Such tactile interference effects do not merely reflect the consequences of sensory masking, since an attentional component to the effect has also been identified (e.g., Craig, 1974;Evans & Craig, 1991;Horner, 1997Horner, , 2000.…”
mentioning
confidence: 99%
“…Research has typically concentrated on studying masking and tactile perception on the hands and fingers with relatively few studies examining the whole body 14,[24][25][26][27] . Future directions could include testing contralateral masking on more extensive areas of the body, which might reveal unexpected connections between other body parts or within a limb that could shed light on how the three-dimensional body is represented within the brain.…”
Section: Discussionmentioning
confidence: 99%